Legal Protection for Insurance Consumers in Cases of Default by Insurance Companies Based on the Consumer Protection Act - Andri; Herman, KMS (Jurnal Greenation Sosial dan Politik, 2025)
This study aims to analyze the form of legal protection provided to insurance consumers in cases of default by insurance companies, by referring to the provisions of Law Number 8 of 1999 concerning Consumer Protection. In practice, default cases often result in material and immaterial losses for policyholders, as well as legal uncertainty. Through a normative legal approach, this study examines the rights and obligations of the parties in the insurance agreement and the role of the supervisory institution in ensuring the fulfillment of consumer rights. The results of the study indicate that although there are regulations governing consumer protection, their implementation still faces various obstacles, especially in terms of law enforcement and dispute-resolution mechanisms. Therefore, it is necessary to strengthen regulations and optimize the role of the Financial Services Authority and the National Consumer Protection Agency in providing effective and fair legal protection for insurance consumers.